Stabilitas Harga Beras dan Efisiensi Distribusi di Provinsi Sumatera Selatan - Ema Pusvita; Lisa Hermawati; Gribaldi (Perum BULOG, 2026)
Background: Rice is a strategic food commodity that plays a vital role in maintaining food security and economic stability. South Sumatra Province is one of the nation’s major rice-producing regions, with production levels that generally result in a surplus. However, fluctuations in consumer rice prices still occur.Objective: This study aims to analyze rice price stability as well as the relationship between price stability and rice distribution efficiency in South Sumatra Province. Method: This study employs a quantitative approach using descriptive and analytical methods. The data utilized consists of secondary data, including monthly medium-grade rice prices, rice production, and rice distribution data in South Sumatra Province for the period 2021–2024.Results and Discussion: Price stability was analyzed using the coefficient of variation (CV), distribution efficiency was analyzed through the marketing margin and farmer’s share, while the relationship between price stability and distribution efficiency was analyzed using multiple linear regression. The results of the study indicate that the price of medium-grade rice increased from Rp10,151/kg in 2021 to Rp11,650/kg in 2024. The coefficient of variation for prices ranged from 0.79–1.53 percent, indicating relatively stable prices. The marketing margin increased from Rp1,761/kg to Rp2,330/kg, while the farmer’s share decreased from 83.27% to 80.00%.Conclusion: The regression results indicate that the marketing margin and distribution costs